New relaxed stability and stabilization conditions for differential linear repetitive processes. Issue 2 (2020) - Maniarski, Robert; Paszke, Wojciech; Rogers, Eric; Boski, Marcin
Abstract: The paper develops new results on the stability analysis of differential linear repetitive processes. These processes are a distinct class of two-dimensional systems that arise in the modelling of physical processes and also the existing systems theory for them can be used to effect in solving control problems for other classes of systems, including iterative learning control design. This paper uses a version of the Kalman-Yakubovich-Popov Lemma to develop relaxed conditions for the stability property in terms of linear matrix inequalities. The main result is reduced conservatism in applying tests for the stability property with an extension to control law design. A numerical example to illustrate the application of the new results is also given.